PEG-modification on the endo-position of an antisense oligonucleotide increases tumor accumulation via the EPR effect. Issue 4 (4th March 2018) - Hagiwara, Kenji; Kurihara, Kana; Honma, Masakazu; Yamamoto, Junichiro; Shinohara, Fumikazu
Abstract: Nucleic acid medicine is the next-generation therapeutic modality for refractory diseases with its unique mode of action as an alternative to traditional therapies. A nucleic acid delivery system targeted to liver was validated clinically; however, the delivery system of nucleic acids targeting solid tumors following systemic administration is not efficient enough for clinical use. In this study, we first utilized an antisense oligonucleotide (ASO) and polyethylene glycol (PEG) in one-to-one conjugation (PEG-ASO) at the endo-position of the ASO (endo-PEG-ASO). The effects of ASO modification position, PEG structure and molecular weight, and PEG-ASO tumor accumulation were evaluated in vivo . The endo-PEG-ASO showed prolonged pharmacokinetics and enhanced tumor accumulation compared with the conventional ASO and the PEG-ASO modified at the ASO exo-position (exo-PEG-ASO), indicating that the modification position of PEG is crucial for targeting tumors. We also observed that the endo-PEG-ASO indicated possibility of enhanced permeability inside the tumor. Further research is needed to optimize the linker in the endo-PEG-ASO for clinical application as a novel and promising therapeutic format for targeting solid tumors.